2022
DOI: 10.1002/osp4.604
|View full text |Cite
|
Sign up to set email alerts
|

Parents of minor children lose less weight during a behavioral weight loss intervention: Findings from the Rural LEAP trial

Abstract: Objective:The transition to parenthood is associated with worsening health behaviors, yet the impact of parental status on successful weight loss has rarely been examined. The purpose of this study was to examine the effect of parental status of minor children on weight loss and behavioral adherence in a rural community-based weight loss intervention. Methods: Five hundred and twenty-eight adults (age 21-75 years, body mass index [BMI] 30-45 kg/m 2 ) were enrolled in a group-based weight loss intervention cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Previous findings suggest that being a parent can influence attitudes and practices in weight management strategies. For example, a study found that parents of minor children had poorer weight loss outcomes and behavioural adherence, than participants without children, in a rural community-based weight loss intervention [ 45 ]. Therefore, the differences in our study compared with Harring et al [ 44 ] is likely attributed to the difference samples (community-dwelling adults who were parents of school-aged children, versus college students).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings suggest that being a parent can influence attitudes and practices in weight management strategies. For example, a study found that parents of minor children had poorer weight loss outcomes and behavioural adherence, than participants without children, in a rural community-based weight loss intervention [ 45 ]. Therefore, the differences in our study compared with Harring et al [ 44 ] is likely attributed to the difference samples (community-dwelling adults who were parents of school-aged children, versus college students).…”
Section: Discussionmentioning
confidence: 99%